A standardised neurosurgical referral letter for the inter-hospital transfer of head injured patients. Issue 4 (1st July 2000) - Keaney, J; Fitzpatrick, M O; Beard, D; Ritchie, D A W; Dunn, L T
Abstract : Objectives —(1) To evaluate the use of a standardised neurosurgical referral letter in terms of compliance, completeness and clinical relevance. (2)To compare the clinical information provided on the standardised neurosurgical letter with that provided by referring hospitals that used alternative documentation. Design —A six month prospective audit was conducted in south west Scotland. Consultant neurosurgeons were asked to weight key clinical variables on the neurosurgical referral letter (NRL). Postal surveys of 114 referring accident and emergency (A&E) staff and 18 neurosurgical receiving staff were undertaken to determine the clinical relevance of the NRL. Case notes were examined for the presence and level of completeness of the NRL. In the absence of the NRL, a form was completed retrospectively using data from the referring hospital's letter. This enabled comparison of the NRL with routine hospital letters in terms of the availability of key clinical information. Results —139 adult patients were identified as suitable for inclusion: 99 patients were transferred from 11 hospitals with access to the NRL. The compliance rate for use of the NRLwas 82%. Forty patients were transferred from nine hospitals that did not have access to the NRL. The completion rate of key variables on the NRL was higher than when an ordinary letter was sent: 87% compared with 38%. The NRL was considered useful by 67 of 71 (94%) A&E questionnaire respondents and by 14 of 15 neurosurgeons who responded. Conclusions —The widespread acceptance of the NRL and its ability to provide essential clinical information in a concise format not available in routine hospital letters indicates that national, standardised documentation can be implemented if users are involved in both its design and implementation.